In-Vitro culture and Cryconservation of Epidendrum gender polineos in the Province of Imbabura - López Flores, Maria Fernando (2019)
The genus Epidendrum of the Family Orchidaceae is a group of plants native to Ecuador. It is a genus of plants that can withstand a great difference from heat temperatures to cold temperatures. It is characterized by large inflorescences that carry dozens of tiny but very elaborate flowers. He is currently in a vulnerable state due to natural disasters (forest fires) and the anthropic action of man (indiscriminate logging) in the country; for this reason, it was considered to carry out an in vitro propagation for the conservation of this species. Therefore, different plots were carried out that determined the incidence of this genus in the community of Morochos, Province of Imbabura. In addition, an in vitro culture protocol was developed from young leaves, buds and seeds; these were seeded in a culture medium prepared of Murashige and Skoog in full concentration (4.3g. l-1), sucrose (30g.l-1), agar (10g.l-1), supplemented with acid antioxidants citric and ascorbic acid (100mg.l-1), in addition to growth regulating hormones ANA and BAP (10 mg. l-1). After 120 days of sowing in vitro, the formation of buds, the length and survival of the explant were evaluated in each of the treatments (young leaves, buds and seeds). The best treatment being that of the seeds, because it obtained the best results compared to the other explants (yolks and young leaves). Finally, the polynes were conserved in liquid nitrogen for later evaluation of viability.